Exploring the thermoelectric properties of oligo(phenylene-ethynylene) derivatives. Issue 28 (13th July 2020) - Chen, Hang; Sangtarash, Sara; Li, Guopeng; Gantenbein, Markus; Cao, Wenqiang; Alqorashi, Afaf; Liu, Junyang; Zhang, Chunquan; Zhang, Yulong; Chen, Lijue; Chen, Yaorong; Olsen, Gunnar; et al.
Abstract : Seebeck coefficient measurements provide unique insights into the electronic structure of single-molecule junctions. Abstract : Seebeck coefficient measurements provide unique insights into the electronic structure of single-molecule junctions, which underpins their charge and heat transport properties. Since the Seebeck coefficient depends on the slope of the transmission function at the Fermi energy ( E F ), the sign of the thermoelectric voltage will be determined by the location of the molecular orbital levels relative to E F . Here we investigate thermoelectricity in molecular junctions formed from a series of oligophenylene-ethynylene (OPE) derivatives with biphenylene, naphthalene and anthracene cores and pyridyl or methylthio end-groups. Single-molecule conductance and thermoelectric voltage data were obtained using a home-built scanning tunneling microscope break junction technique. The results show that all the OPE derivatives studied here are dominated by the lowest unoccupied molecular orbital level. The Seebeck coefficients for these molecules follow the same trend as the energy derivatives of their corresponding transmission spectra around the Fermi level. The molecule terminated with pyridyl units has the largest Seebeck coefficient corresponding to the highest slope of the transmission function at E F . Density-functional-theory-based quantum transport calculations support the experimental results.